Comprehensive overview of antibody drug-related clinical studies in gynecology: insights from ClinicalTrials.gov - Zhou, Xiaoling; Xiao, Li; Lai, Fan; Chen, Wei; Zhou, Congrong; Deng, Yi; Wang, Tao; Xing, Shasha; Diao, Haoyang; Tang, Mi; Guo, Wenmei; Luo, Erdan (Frontiers in Medicine, 2025)
Antibodies have been widely used globally over the past decade and play an increasingly important role in modern medicine. Notably, significant advancements have been achieved in the realm of gynecology, particularly in gynecological cancers. This study endeavors to present a thorough overview of antibody-related drug clinical studies in gynecology registered on ClinicalTrials.gov, focusing on the basic characteristics of trials, geographical distribution, administration routes, indications, and targets. The analysis indicates a rising prevalence of antibody–drug conjugates (ADCs), bispecific antibodies, and Fc-fusion proteins. This study will help develop new ideas for future research on antibodies in gynecology.